Maternal knowledge on child survival in the poorest areas of North and Northeast Brazil: o caso de áreas pobres nas regiões Norte e Nordeste do Brasil Conhecimento materno em sobrevivência infantil - Juraci A. Cesar; Alessandra C. Diziekaniak; Paula R. P. Ribeiro; Tatiane S. Gonçalves; Nelson A. Neumann (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
This study aimed to evaluate knowledge on child survival among mothers of children under five years of age living in nine municipalities in North and Northeast Brazil. A standardized questionnaire was used for home interviews of mothers visited by volunteers from the Pastorate of the Child and mothers not visited by the program (control areas). The association between independent variables and the outcome (visited versus not visited by the Pastorate of the Child) was evaluated using the chi-square test. Among the 752 mothers studied, 386 were visited by Pastorate of the Child volunteers and 366 were not visited. Mothers visited by the Pastorate of the Child, although poorer, showed better knowledge on monitoring child growth and identifying child development difficulties as compared to mothers from the control areas. Despite the better performance of mothers visited by the Pastorate of the Child volunteers, maternal knowledge on child survival in both groups was less than desirable. This hinders the identification of more serious cases, delays seeking medical care, and reduces the impact on child morbidity and mortality. Este estudo teve por objetivo avaliar o conhecimento em sobrevivência infantil entre mães de menores de cinco anos residentes em nove municípios das regiões Norte e Nordeste do Brasil. Aplicou-se questionário padronizado no domicílio para mães acompanhadas pelos líderes da Pastoral da Criança e não acompanhadas (áreas-controle). A associação entre as variáveis independentes e o desfecho (receber ou não visita dos líderes da Pastoral da Criança) foi avaliada pelo teste do qui-quadrado. Dentre as 752 mães estudadas, 386 eram visitadas pelos líderes da Pastoral da Criança e 366 não eram visitadas. Mães visitadas pelos líderes da Pastoral da Criança, apesar de mais pobres, apresentaram melhor conhecimento sobre monitoração do crescimento infantil, identificação de pneumonia e dificuldade no desenvolvimento em relação às mães das áreas-controle. Apesar do melhor desempenho entre mães visitadas pelos líderes da Pastoral da Criança, o conhecimento materno em sobrevivência infantil para todas elas ficou aquém do desejado. Isso dificulta a identificação dos casos de maior gravidade, retarda a busca de cuidados médicos e reduz o impacto sobre a morbimortalidade infantil.